(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Sevastianova O. Competence approach in vocational training for future teachers of technology. The article outlines the views of the problem of professional competence of the teacher, the structure of the professional competence of teachers of modern technology. The approaches to the definition of «professional competence». Attention is drawn to the essence of innovative technologies like aspect of the preparation of future teachers of technology education.